Superhard scratch-resistant coating for composite material as well as preparation method and application of superhard scratch-resistant coating
Through the cross-linking reaction of organic-inorganic hybrid materials, an ultra-hard scratch-resistant coating with high hardness and toughness was prepared, which solved the problems of surface adhesion of composite materials and the transparency of paint film, and achieved excellent scratch-resistant of composite materials Rub performance and high appearance effect.
Patent Information
- Application Number
- CN202410185200.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2024-12-27
AI Technical Summary
It is difficult to adhere to the surface of existing composite coatings, which are difficult to have high hardness and toughness. The addition of powder causes the paint film to become foggy and opaque, which cannot meet the high appearance needs.
Using organic-inorganic hybrid materials as film forming substances, super hard scratch-resistant coatings are prepared by controlling the crosslinking reaction ratio, and the composition includes aminosilane resin, hydroxyacrylic resin, low boiling point solvent, leveling agent, isocyanate, and high boiling point solvent. and water repellent to form a completely transparent paint film suitable for composite surfaces.
It achieves good adhesion and excellent scratch resistance on the surface of the composite material, reduces the risk of paint film cracking, and meets the needs of high-appearance applications such as automobiles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of coating preparation, and in particular to a superhard scratch-resistant coating for composite materials and a preparation method and application thereof. Background Art
[0002] Composite materials have excellent properties such as light weight, high strength, intelligence, multi-function, and green environmental protection, and can be widely used in the automotive industry, electronics, aerospace, rail transportation, wind power and new energy, etc. In recent years, the market demand for composite materials has continued to grow, and the industry has broad prospects for development.
[0003] According to the different matrix materials, composite materials can be divided into resin-based composite materials, ceramic-based composite materials, metal-based composite materials, etc. Among them, resin-based composite materials have become the most widely used and fastest-growing composite materials due to their advantages such as low density, high specific strength and specific modulus, high fatigue strength, good damage safety characteristics, strong corrosion resistance and heat resistance, good dielectric properties and electromagnetic wave permeability, accounting for more than 80% of composite materials. In some application scenarios that require ultra-high hardness and excellent appearance, such as mobile phone back covers, laptops, and auto parts, traditional metal materials have been transformed into composite materials. These application scenarios require coatings to provide excellent appearance and scratch resistance to prevent items from being scratched during use and affecting their beauty and service life.
[0004] In the prior art, it is difficult for the coating to adhere to the surface due to the immature composite material process, many surface defects, and low surface energy of the material. To solve this problem, there are two main ways to improve the scratch resistance of the coating on the market: one is to use inorganic materials to increase the hardness of the paint film, but it is difficult to ensure the flexibility of the paint film while meeting the high hardness, and the possibility of brittle fracture will increase. Hardness refers to the ability of a material to locally resist hard objects from pressing into its surface, while toughness refers to the ability of a material to absorb energy during plastic deformation and fracture. Hardness and toughness are a pair of contradictions. Generally, the higher the hardness of the material, the worse the toughness, and the better the toughness, the lower the relative hardness. The second is to add polytetrafluoroethylene wax powder to improve the scratch resistance of the paint film, but the addition of powder will cause the paint film to become foggy and opaque, which cannot meet the application scenarios of high appearance such as automobiles.
[0005] In view of this, there is an urgent need in the art to develop a coating with excellent adhesion to the surface of a composite material, which has both hardness and toughness and can have an excellent appearance, so as to solve the problems faced in the prior art. Summary of the invention
[0006] Based on the above facts, the present invention aims to provide a super-hard scratch-resistant coating for composite materials, which uses organic-inorganic hybrid materials as film-forming substances, and controls the cross-linking reaction ratio to make the paint film have both super-high hardness and toughness, and has good adhesion on the surface of the composite material. It does not contain powder additives, the paint film is completely transparent, can achieve the effect of Class A surface, and is suitable for high-appearance application scenarios such as automobiles.
[0007] A first aspect of the present invention provides an ultra-hard scratch-resistant coating for a composite material, comprising component A and component B, wherein, by weight, component A comprises 10-100 parts of an aminosilane resin, 0-30 parts of a hydroxyl acrylic resin, 0-30 parts of a low boiling point solvent, 0.1-2 parts of a leveling agent, and 0.1-3 parts of an external additive; component B comprises 40-90 parts of an isocyanate, 20-50 parts of a high boiling point solvent, and 0-5 parts of a water-repellent; and the weight ratio of component A to component B is any ratio between 1:1 and 10:1.
[0008] In the present invention, the composite material refers to a material with new properties that is composed of two or more materials with different properties through physical or chemical methods at the macroscopic or microscopic level.
[0009] Aminosilane resin
[0010] In the present invention, the aminosilane resin is selected from one or more of bis(trimethoxysilylpropyl)amine, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminoethylaminopropyltrimethoxysilane, and polyaminoalkyltrialkoxysilane.
[0011] Hydroxylated acrylic resin
[0012] In the present invention, the hydroxylated acrylic resin is a primary or secondary dispersion of an aqueous polyhydroxylated acrylic resin.
[0013] Low boiling point solvent
[0014] In the present invention, the low boiling point solvent is selected from one or more of diethyl ether, acetone, ethyl acetate and methanol.
[0015] Leveling agent
[0016] In the present invention, the leveling agent is selected from one or more of polydimethylsiloxane, polyether or polyester modified siloxane, acrylate, and alkyl modified organic siloxane. The use of the leveling agent can make the paint film have a better leveling effect on the surface of the composite material.
[0017] Additional additives
[0018] In the present invention, the additional auxiliary agent is selected from one or more of a wetting agent, a defoaming agent, a UV absorber, and a thickener.
[0019] Isocyanate
[0020] In the present invention, the isocyanate is selected from one or more of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), and lysine diisocyanate (LDI).
[0021] High boiling point solvent
[0022] In the present invention, the high boiling point solvent is selected from one or more of propylene glycol methyl ether acetate (PMA), ethylene glycol butyl ether, propylene glycol methyl ether, dibasic acid esters, and propylene glycol diacetate.
[0023] Water repellent
[0024] In the present invention, the water-repellent is selected from one or more of lignin sulfonate, naphthalene sulfonate formaldehyde polymer, silicate, and phosphate. The water-repellent can eliminate the water in the coating through chemical reaction.
[0025] The second aspect of the present invention provides a method for preparing the ultra-hard scratch-resistant coating for composite materials according to the first aspect of the present invention, comprising the following steps:
[0026] (1) Under stirring, aminosilane resin, hydroxy acrylic resin, low boiling point solvent, leveling agent and additional additives are sequentially added to container A, and stirred at a stirring rate of 500-1500 r / min for 15-20 min to mix uniformly to obtain component A;
[0027] (2) under stirring, add isocyanate, high boiling point solvent and water displacing agent to container B in sequence, stir at a stirring rate of 300-1000 r / min for 10-20 min, and mix them evenly to obtain component B;
[0028] (3) When in use, component A and component B are fully mixed according to a certain proportion to obtain the superhard scratch-resistant coating for composite materials.
[0029] The third aspect of the present invention provides an application of the superhard scratch-resistant coating for composite materials according to the first aspect of the present invention, comprising the following steps:
[0030] The super-hard scratch-resistant coating for composite materials is applied to the composite materials, and heated and cured at a temperature of 20-120° C. for 0.5-24 hours; preferably, the heating and curing temperature is 80° C. and the curing time is 40-60 minutes.
[0031] The composite material is preferably a carbon fiber composite material or a glass fiber composite material; more preferably, the carbon fiber composite material is a composite material formed by combining carbon fiber and epoxy resin, and the glass fiber composite material is a composite material with glass fiber reinforced unsaturated polyester, epoxy resin and phenolic resin as matrix materials.
[0032] The beneficial effects of the present invention are as follows:
[0033] The present invention provides a super-hard scratch-resistant coating for composite materials, which uses an organic-inorganic hybrid material as a film-forming substance, and increases the hardness of the coating while increasing flexibility by controlling the cross-linking reaction ratio, so that the paint film has good adhesion on the surface of the composite material, has excellent scratch resistance and reduces the risk of cracking of the paint film. In addition, the super-hard scratch-resistant coating does not contain powder additives, the paint film is completely transparent, can achieve the effect of Class A surface, and is suitable for high-appearance application scenarios such as automobiles. DETAILED DESCRIPTION
[0034] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with specific examples and comparative examples. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified, and the raw materials and reagents used are products that can be purchased from conventional commercial channels unless otherwise specified.
[0035] The above technical solution is described below in conjunction with specific embodiments.
[0036] Example 1: Ultra-hard scratch-resistant coating for composite materials 1
[0037] The superhard scratch-resistant coating 1 for composite materials is prepared according to the formula in Table 1 below, and the preparation steps are as follows:
[0038] (1) Under stirring, aminosilane resin, hydroxy acrylic resin, low boiling point solvent, leveling agent and additional additives are sequentially added to container A, and stirred at a stirring rate of 500-1500 r / min for 15-20 min to mix uniformly to obtain component A;
[0039] (2) under stirring, add isocyanate, high boiling point solvent and water displacing agent to container B in sequence, stir at a stirring rate of 300-1000 r / min for 10-20 min, and mix them evenly to obtain component B;
[0040] (3) When in use, component A and component B are fully mixed according to a certain proportion to obtain the superhard scratch-resistant coating 1 for composite materials.
[0041] Table 1 Raw material components of the superhard scratch-resistant coating 1 for composite materials in Example 1
[0042]
[0043]
[0044] The super-hard scratch-resistant coating 1 for composite materials was coated on tinplate and carbon fiber composite materials and cured at 80°C for 60 minutes before performance testing. The test results are shown in Table 4.
[0045] Example 2: Ultra-hard scratch-resistant coating for composite materials 2
[0046] The superhard scratch-resistant coating 2 for composite materials was prepared according to the formula in Table 2 below, and the preparation steps were the same as those in Example 1.
[0047] Table 2 Raw material components of superhard scratch-resistant coating 2 for composite materials in Example 2
[0048]
[0049] The super-hard scratch-resistant coating 2 for composite materials was coated on tinplate and carbon fiber composite materials and cured at 80°C for 60 minutes before performance testing. The test results are shown in Table 4.
[0050] Example 3: Ultra-hard scratch-resistant coating for composite materials 3
[0051] The superhard scratch-resistant coating 3 for composite materials was prepared according to the formula in Table 3 below, and the preparation steps were the same as those in Example 1.
[0052] Table 3 Raw material components of superhard scratch-resistant coating 3 for composite materials in Example 3
[0053]
[0054] The super-hard scratch-resistant coating 3 for composite materials was coated on tinplate and carbon fiber composite materials and cured at 80°C for 60 minutes before performance testing. The test results are shown in Table 4.
[0055] Table 4 Physical property test results of superhard scratch-resistant coatings 1-3 for composite materials in Examples 1-3
[0056]
[0057] Comparative Example 1: Coating 1 as a comparative example
[0058] Coating 1 as a comparative example was prepared according to the formulation in Table 5 below, and the preparation steps were the same as those in Example 1.
[0059] Table 5 Raw material components of coating 1 used as comparative example in comparative example 1
[0060]
[0061] The coating 1 used as a comparative example was applied to the tinplate and carbon fiber composite material, and cured at 80° C. for 60 minutes before the performance test was carried out. The test results are shown in Table 8.
[0062] It should be noted that in the coating 1 as a comparative example, the weight ratio of component A to component B is too high, which is not within the scope of protection of the present invention, so it is comparative example 1. If the weight ratio of component A to component B is too high, the paint film cannot be completely cross-linked, the hardness can only reach H, and the paint film has no adhesion on the composite material.
[0063] Comparative Example 2: Coating 2 as a comparative example
[0064] Coating 2 as a comparative example was prepared according to the formula in Table 6 below, and the preparation steps were the same as those in Example 1.
[0065] Table 6 Raw material components of coating 2 used as comparative example in comparative example 2
[0066]
[0067] The coating 2 used as a comparative example was applied to the tinplate and carbon fiber composite material, and cured at 80° C. for 60 minutes before conducting a performance test. The test results are shown in Table 8.
[0068] It should be noted that, in the coating 2 as comparative example, the dosage of hydroxy acrylic resin and low boiling point solvent is too high, which is not within the scope of protection of the present invention, so it is comparative example 2. Excessive dosage of hydroxy acrylic resin and low boiling point solvent will lead to easy blistering during the drying process of the paint film, the hardness of the paint film cannot reach more than 2H, and the scratch resistance effect is extremely poor.
[0069] Comparative Example 3: Coating 3 as a comparative example
[0070] Coating 3 as a comparative example was prepared according to the formula in Table 7 below, and the preparation steps were as follows:
[0071] (1) Under stirring, aminosilane resin, epoxy resin, low boiling point solvent, leveling agent and additional additives are added to container A in sequence, and stirred at a stirring rate of 500-1500 r / min for 15-20 min to mix uniformly to obtain component A;
[0072] (2) under stirring, add isocyanate, high boiling point solvent and water displacing agent to container B in sequence, stir at a stirring rate of 300-1000 r / min for 10-20 min, and mix them evenly to obtain component B;
[0073] (3) When using, component A and component B are fully mixed according to the proportion to obtain coating 3 as a comparative example.
[0074] Table 7 Raw material components of coating 3 used as comparative example in comparative example 3
[0075]
[0076] The coating 3 used as a comparative example was coated on the tinplate and carbon fiber composite material, and cured at 80° C. for 60 minutes before the performance test was carried out. The test results are shown in Table 8.
[0077] It should be noted that in the coating 3 as comparative example, the epoxy resin does not belong to the hydroxy acrylic resin and is not within the protection scope of the present invention, so it is comparative example 3. Using epoxy resin instead of hydroxy acrylic resin will lead to poor adhesion and flexibility of the paint film, and the paint film will crack after 8 hours of heat and humidity resistance.
[0078] Table 8 Physical property test results of coatings 1-3 used as comparative examples in comparative examples 1-3
[0079]
[0080] From the results in Tables 4 and 8, it can be seen that the superhard scratch-resistant coatings 1-3 for composite materials obtained in Examples 1-3 have formed coatings that are superhard and scratch-resistant, and have good performance in hardness, moisture and heat resistance, flexibility, and adhesion to the substrate, and can ensure long-term use on the composite materials. However, the coatings formed by the coatings 1-3 obtained in Comparative Examples 1-3 have defects in hardness, moisture and heat resistance, flexibility, and adhesion to the substrate, and cannot ensure long-term use on the composite materials.
[0081] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A superhard scratch-resistant coating for a composite material, comprising component A and component B, wherein component A comprises 10-100 parts of an aminosilane resin, 0-30 parts of a hydroxy acrylic resin, 0-30 parts of a low boiling point solvent, 0.1-2 parts of a leveling agent, and 0.1-3 parts of an external additive, by weight; component B comprises 40-90 parts of an isocyanate, 20-50 parts of a high boiling point solvent, and 0-5 parts of a water-repellent; and the weight ratio of component A to component B is any ratio between 1:1 and 10:
1.
2. The superhard scratch-resistant coating for composite materials according to claim 1, characterized in that: The aminosilane resin is selected from one or more of bis(trimethoxysilylpropyl)amine, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminoethylaminopropyltrimethoxysilane and polyaminoalkyltrialkoxysilane.
3. The superhard scratch-resistant coating for composite materials according to claim 1, characterized in that: The hydroxylated acrylic resin is a primary or secondary dispersion of an aqueous polyhydroxylated acrylic resin.
4. The superhard scratch-resistant coating for composite materials according to claim 1, characterized in that: The low boiling point solvent is selected from one or more of ether, acetone, ethyl acetate, and methanol, and the high boiling point solvent is selected from one or more of propylene glycol methyl ether acetate (PMA), ethylene glycol butyl ether, propylene glycol methyl ether, dibasic acid esters, and propylene glycol diacetate.
5. The superhard scratch-resistant coating for composite materials according to claim 1, characterized in that: The leveling agent is selected from one or more of polydimethylsiloxane, polyether or polyester modified siloxane, acrylate, alkyl modified organosiloxane, the additional auxiliary agent is selected from one or more of wetting agent, defoamer, UV absorber, thickener, and the water repellent is selected from one or more of lignin sulfonate, naphthalene sulfonate formaldehyde polymer, silicate, and phosphate.
6. The superhard scratch-resistant coating for composite materials according to claim 1, characterized in that: The isocyanate is selected from one or more of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), and lysine diisocyanate (LDI).
7. A method for preparing a superhard scratch-resistant coating for composite materials according to any one of claims 1 to 6, characterized in that: The steps include: (1) Under stirring, aminosilane resin, hydroxy acrylic resin, low boiling point solvent, leveling agent and additional additives are sequentially added to container A, and stirred at a stirring rate of 500-1500 r / min for 15-20 min to mix uniformly to obtain component A; (2) under stirring, add isocyanate, high boiling point solvent and water displacing agent to container B in sequence, stir at a stirring rate of 300-1000 r / min for 10-20 min, and mix them evenly to obtain component B; (3) When in use, component A and component B are fully mixed according to a certain proportion to obtain the superhard scratch-resistant coating for composite materials.
8. An application of the superhard scratch-resistant coating for composite materials according to any one of claims 1 to 6, characterized in that: The steps include: The super-hard scratch-resistant coating for composite materials is applied to the composite materials, and heated and cured at a temperature of 20-120° C. for 0.5-24 hours; preferably, the heating and curing temperature is 80° C. and the curing time is 40-60 minutes.
9. The use of the superhard scratch-resistant coating for composite materials according to claim 8, characterized in that: The composite material is preferably a carbon fiber composite material or a glass fiber composite material; more preferably, the carbon fiber composite material is a composite material formed by combining carbon fiber and epoxy resin, and the glass fiber composite material is a composite material with glass fiber reinforced unsaturated polyester, epoxy resin and phenolic resin as matrix materials.
